Open Access

A sharpened version of Hardy’s inequality for parameter p = 5 / 4

Journal of Inequalities and Applications20132013:63

DOI: 10.1186/1029-242X-2013-63

Received: 10 December 2012

Accepted: 1 February 2013

Published: 20 February 2013

Abstract

The purpose of this paper is to investigate a sharpened version of Hardy’s inequality for parameter p = 5 / 4 . By evaluating the weight coefficient W ( k , 5 / 4 ) , sharpened Hardy’s inequality that contains the best coefficient η 5 / 4 = 0.46 is established.

MSC:26D15, 26D20, 26D07.

Keywords

Hardy’s inequality weight coefficient sharpened inequality exponential parameter best coefficient

1 Introduction

Let p > 1 , 1 / p + 1 / q = 1 , a n 0 ( n = 1 , 2 , ), 0 < n = 1 a n p < . Then
n = 1 ( 1 n k = 1 n a k ) p < q p n = 1 a n p ,
(1)

where q p = ( p p 1 ) p is the best coefficient. Inequality (1) is called Hardy’s inequality which is of great use in the field of modern mathematics (see [1, 2]).

A special case of (1) yields the following inequalities:
n = 1 ( 1 n k = 1 n a k ) 2 < 4 n = 1 a n 2 ,
(2)
n = 1 ( 1 n k = 1 n a k ) 3 < 27 8 n = 1 a n 3 .
(3)
In 1998, Yang and Zhu [3] evaluated the weight coefficient W ( k , p ) ,
W ( k , p ) = k 1 1 / p n = k 1 n p ( j = 1 n 1 j 1 / p ) p 1 , k = 1 , 2 , ,
(4)
and established an improved version of inequality (2) as follows:
n = 1 ( 1 n k = 1 n a k ) 2 < 4 n = 1 ( 1 1 3 n + 5 ) a n 2 .
(5)
With the same approach, that is, evaluating the weight coefficient W ( k , p ) , Huang [47] gave some improvements on Hardy’s inequality for p = 3 and p = 3 / 2 , i.e.,
n = 1 ( 1 n k = 1 n a k ) 3 < 27 8 n = 1 ( 1 3 19 n 2 / 3 ) a n 3 ,
(6)
n = 1 ( 1 n k = 1 n a k ) 3 / 2 3 3 n = 1 ( 1 1 5 1 n 3 + 3 ) a n 3 / 2 .
(7)

Some further extensions of Hardy’s inequality related to the range of parameter p were given in Huang [7, 8].

In 2005, Yang [9] proved an inequality for the weight coefficient W ( k , 2 )
W ( k , 2 ) = k n = k 1 n 2 ( j = 1 n 1 j ) 4 [ 1 1 k ( 1 1 4 W ( 1 , 2 ) ) ]
and established the following inequality:
n = 1 ( 1 n k = 1 n a k ) 2 < 4 n = 1 ( 1 θ 2 n ) a n 2 ,
(8)

where θ 2 = 1 1 4 W ( 1 , 2 ) = 0.13788928 is the best coefficient under the weight coefficient W ( k , 2 ) .

In 2009, Zhang and Xu made use of the monotonicity theorem [1013] and obtained an improvement of inequality (1):
n = 1 ( 1 n k = 1 n a k ) p ( p p 1 ) p n = 1 ( 1 c p 2 ( n 1 / 2 ) 1 1 / p ) a n p ,
(9)
where
c p = { ( p 1 ) [ 1 2 1 / p ( 1 1 / p ) ] , 1 < p 2 , 1 2 1 1 / p ( 1 1 / p ) p 1 , p > 2 .
By evaluating the weight coefficient W ( k , p ) , and with the help of an inequality-proving package called BOTTEMA [14, 15], He [16] investigated a sharpened version of Hardy’s inequality for p N and obtained the following improved version of inequality (3):
n = 1 ( 1 n k = 1 n a k ) 3 27 8 n = 1 ( 1 θ 3 n 2 / 3 ) a n 3 ,
(10)

where θ 3 = 1 8 27 W ( 1 , 3 ) = 0.1673 is the best coefficient under the weight coefficient W ( k , 3 ) .

In addition, in [16] the author wrote the computer program HDISCOVER to accomplish the automated verification of the following inequality for p N (N is the set of natural numbers):
n = 1 ( 1 n k = 1 n a k ) p ( p p 1 ) p n = 1 ( 1 θ p ( 1 ) n 1 1 / p ) a n p ,
(11)

where θ p ( 1 ) = 1 ( p 1 p ) p W ( 1 , p ) is the best coefficient of (11) under the weight coefficient W ( k , p ) .

Recently, based on the program HDISCOVER 2012 written by Deng, He and Wu [17], an automated verification of inequality (11) is achieved for p Q (Q is the set of rational numbers).

For more detailed information of Hardy’s inequality, we refer the interested readers to relevant research papers [10, 12, 1823].

In this paper, by evaluating the weight coefficient W ( k , 5 / 4 ) , we establish an improvement of Hardy’s inequality for parameter p = 5 / 4 as follows:
n = 1 ( 1 n k = 1 n a k ) 5 / 4 5 5 / 4 n = 1 ( 1 1 10 1 n 1 / 5 + η 5 / 4 ) a n 5 / 4 ,
(12)

where η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.46 is the best coefficient under the weight coefficient W ( k , 5 / 4 ) .

2 Lemmas

To prove the main results in Section 3, we will use the following lemmas.

Lemma 1 (see[22])

If p > 1 , then for all integers n 1 , it holds that
p p 1 n 1 1 / p p p 1 + 1 2 + 1 2 n 1 / p j = 1 n 1 j 1 / p p p 1 n 1 1 / p p p 1 + 1 2 + 1 2 n 1 / p + 1 12 p 1 12 p n 1 + 1 / p .
(13)

Lemma 2 (see[3])

If p > 1 , then for all integers n k 1 , it holds that
1 ( p 1 ) k p 1 + 1 2 k p < n = k 1 n p < 1 ( p 1 ) k p 1 + 1 2 k p + p 12 k p + 1 .
Lemma 3 Let p > 1 , 1 / p + 1 / q = 1 , and let g r , g l be the functions defined by
g r ( x ) = 6 p + 12 q 1 12 p q x 1 / q + 1 2 q x 1 12 p q x 2 , g l ( x ) = p + 2 q 2 p q x 1 / q + 1 2 q x , x [ 1 , + ) .

Then 1 < g r ( x ) < 0 , 1 < g l ( x ) < 0 .

Proof Since p > 1 , 1 / p + 1 / q = 1 , hence 1 / x 1 + 1 / p 1 / x 2 for x [ 1 , + ) .

Further, we have
g r ( x ) = 6 p + 12 q 1 12 p q 2 x 1 + 1 / q 1 2 q x 2 + 1 6 p q x 3 6 p + 12 q 1 12 p q 2 x 2 1 2 q x 2 + 1 6 p q x 3 = ( 5 p x + x + 2 p ) ( p 1 ) 12 p 3 x 3 > 0 ,

and consequently, g r is strictly increasing on [ 1 , + ) .

Now, from g r ( 1 ) = 1 / p > 1 and lim x + g r ( x ) = 0 , it follows that g r ( x ) g r ( 1 ) = 1 / p > 1 and g r ( x ) < 0 .

Similarly, from
g l ( x ) = p + 2 q 2 p q 2 x 1 + 1 / q 1 2 q x 2 p + 2 q 2 p q 2 x 2 1 2 q x 2 = p 1 2 p 2 x 2 > 0 , g l ( 1 ) = 1 / p > 1 and lim x + g l ( x ) = 0 ,

we deduce that 1 < g l ( x ) < 0 .

Lemma 3 is proved. □

Lemma 4 Let 1 < g ( x ) < 0 . If α ( 0 , 1 ] , then
( 1 + g ( x ) ) ( 1 + ( α 1 ) g ( x ) + ( α 1 ) ( α 2 ) 2 g 2 ( x ) ) ( 1 + g ( x ) ) α 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) .
If α [ 1 , 2 ] , then
( 1 + g ( x ) ) α 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) .
Proof When α ( 0 , 1 ] . By using the Maclaurin formula
( 1 + g ( x ) ) α = 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) + α ( α 1 ) ( α 2 ) ( 1 + θ g ( x ) ) α 3 6 g 3 ( x ) , θ ( 0 , 1 ) ,
and noticing 1 < g ( x ) < 0 , we find
1 + θ g ( x ) > 1 + g ( x ) > 0 , α ( α 1 ) ( α 2 ) ( 1 + θ g ( x ) ) α 3 6 g 3 ( x ) 0 , ( α 1 ) ( α 2 ) ( α 3 ) ( 1 + θ g ( x ) ) α 4 6 g 3 ( x ) 0 .
Thus
( 1 + g ( x ) ) α 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) , ( 1 + g ( x ) ) α = ( 1 + g ( x ) ) ( 1 + g ( x ) ) α 1 ( 1 + g ( x ) ) ( 1 + ( α 1 ) g ( x ) + ( α 1 ) ( α 2 ) 2 g 2 ( x ) ) .
When α [ 1 , 2 ] . We have
α ( α 1 ) ( α 2 ) ( 1 + θ g ( x ) ) α 3 6 g 3 ( x ) 0 .
Thus
( 1 + g ( x ) ) α 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) .

The proof of Lemma 4 is complete. □

Lemma 5 Let p > 1 , 1 / p + 1 / q = 1 , n k 1 , and let [ x ] denote the greatest integer less than or equal to the real number x. Then we have
W ( k , p ) q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g r ( n ) ) [ p ] 1 × ( 1 + ( p [ p ] ) g r ( n ) + ( p [ p ] ) ( p [ p ] 1 ) 2 g r 2 ( n ) ) ] .
Proof By Lemma 1 and the identity p q = p + q , q ( p 1 ) = p , it follows that
W ( k , p ) = k 1 1 / p n = k 1 n p ( j = 1 n 1 j 1 / p ) p 1 k 1 1 / p n = k 1 n p ( p p 1 n 1 1 / p p p 1 + 1 2 + 1 2 n 1 / p + 1 12 p 1 12 p n 1 + 1 / p ) p 1 = k 1 / q n = k 1 n p ( q n 1 / q 6 p + 12 q 1 12 p + 1 2 n 1 / p 1 12 p n 1 + 1 / p ) p 1 = k 1 / q n = k 1 n p q p 1 n ( p 1 ) / q ( 1 6 p + 12 q 1 12 p q n 1 / q + 1 2 q n 1 12 p q n 2 ) p 1 = q p 1 k 1 / q n = k 1 n 1 + 1 / q ( 1 + g r ( n ) ) p 1 .
Combining Lemmas 3 and 4, we obtain
W ( k , p ) q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g r ( n ) ) [ p ] 1 ( 1 + g r ( n ) ) p [ p ] ] q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g r ( n ) ) [ p ] 1 × ( 1 + ( p [ p ] ) g r ( n ) + ( p [ p ] ) ( p [ p ] 1 ) 2 g r 2 ( n ) ) ] .

This completes the proof of Lemma 5. □

Lemma 6 Let 1 / p + 1 / q = 1 , n k 1 . If p ( 1 , 2 ) , then
W ( k , p ) q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] × ( 1 + ( p [ p ] 1 ) g l ( n ) + ( p [ p ] 1 ) ( p [ p ] 2 ) 2 g l 2 ( n ) ) ] .
If p [ 2 , + ) , then
W ( k , p ) q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] 2 × ( 1 + ( p [ p ] + 1 ) g l ( n ) + ( p [ p ] + 1 ) ( p [ p ] ) 2 g l 2 ( n ) ) ] .
Proof Since p q = p + q , q ( p 1 ) = p , using Lemma 1 gives
W ( k , p ) = k 1 1 / p n = k 1 n p ( j = 1 n 1 j 1 / p ) p 1 k 1 1 / p n = k 1 n p ( p p 1 n 1 1 / p p p 1 + 1 2 + 1 2 n 1 / p ) p 1 = k 1 / q n = k 1 n p ( q n 1 / q p + 2 q 2 p + 1 2 n 1 / p ) p 1 = k 1 / q n = k 1 n p q p 1 n ( p 1 ) / q ( 1 p + 2 q 2 p q n 1 / q + 1 2 q n ) p 1 = q p 1 k 1 / q n = k 1 n 1 + 1 / q ( 1 + g l ( n ) ) p 1 .
When p ( 1 , 2 ) . From Lemmas 3 and 4, we have
W ( k , p ) q p 1 k 1 / q n = k 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] 1 ( 1 + g l ( n ) ) p [ p ] q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] × ( 1 + ( p [ p ] 1 ) g l ( n ) + ( p [ p ] 1 ) ( p [ p ] 2 ) 2 g l 2 ( n ) ) ] .
When p [ 2 , + ) . Using Lemmas 3 and 4, we obtain
W ( k , p ) q p 1 k 1 / q n = k 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] 2 ( 1 + g l ( n ) ) p [ p ] + 1 q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] 2 × ( 1 + ( p [ p ] + 1 ) g l ( n ) + ( p [ p ] + 1 ) ( p [ p ] ) 2 g l 2 ( n ) ) ] .

Lemma 6 is proved. □

Lemma 7 (see[3])

Let p > 1 , a n 0 ( n = 1 , 2 , ), 0 < n = 1 a n p < . Then
n = 1 ( 1 n k = 1 n a k ) p k = 1 [ k 1 1 / p n = k 1 n p ( j = 1 n 1 j 1 / p ) p 1 a k p ] = k = 1 W ( k , p ) a k p .

3 Main results

Theorem 1 For an arbitrary natural number k, the following inequality holds true:
W ( k , 5 / 4 ) < R 5 / 4 ( k ) ,
where
R 5 / 4 ( k ) = 5 1 / 4 ( 5 133 240 k 1 / 5 17 , 689 144 , 000 k 2 / 5 + 25 48 k 19 192 k 6 / 5 17 , 689 480 , 000 k 7 / 5 + 467 4 , 224 k 2 + 133 18 , 000 k 11 / 5 + 97 38 , 400 k 3 + 133 60 , 000 k 16 / 5 + 61 504 , 000 k 4 + 19 240 , 000 k 5 ) .

Proof

Using Lemma 5 gives
W ( k , 5 / 4 ) 5 1 / 4 k 1 / 5 n = k [ 1 n 6 / 5 ( 1 + 1 4 g r ( n ) 3 32 g r 2 ( n ) ) ] = 5 1 / 4 k 1 / 5 n = k r 5 / 4 ( n ) ,
where
r 5 / 4 ( n ) = 1 n 6 / 5 133 600 n 7 / 5 17 , 689 240 , 000 n 8 / 5 + 1 40 n 11 / 5 + 133 8 , 000 n 12 / 5 41 9 , 600 n 16 / 5 133 60 , 000 n 17 / 5 + 1 4 , 000 n 21 / 5 1 60 , 000 n 26 / 5 .
Hence
W ( k , 5 / 4 ) 5 1 / 4 k 1 / 5 n = k ( 1 n 6 / 5 133 600 n 7 / 5 17 , 689 240 , 000 n 8 / 5 + 1 40 n 11 / 5 + 133 8 , 000 n 12 / 5 41 9 , 600 n 16 / 5 133 60 , 000 n 17 / 5 + 1 4 , 000 n 21 / 5 1 60 , 000 n 26 / 5 ) .
Using Lemma 2 and taking p = 6 / 5 , 7 / 5 , 8 / 5 , 11 / 5 , 12 / 5 , 16 / 5 , 17 / 5 , 21 / 5 , 26 / 5 in the right-hand side of inequality (13), respectively, we get
n = k 1 n 6 / 5 < 5 k 1 / 5 + 1 2 k 6 / 5 + 1 10 k 11 / 5 , n = k 133 600 n 7 / 5 < 133 240 k 2 / 5 133 1 , 200 k 7 / 5 , , n = k 1 4 , 000 n 21 / 5 < 1 12 , 800 k 16 / 5 + 1 8 , 000 k 21 / 5 + 7 80 , 000 k 26 / 5 , n = k 1 60 , 000 n 26 / 5 < 1 252 , 000 k 21 / 5 1 120 , 000 k 26 / 5 .
Adding up the above inequalities, we obtain
W ( k , 5 / 4 ) < R 5 / 4 ( k ) .

Theorem 1 is proved. □

Theorem 2 For an arbitrary natural number k, the following inequality holds true:
W ( k , 5 / 4 ) > L 5 / 4 ( k ) ,
where
L 5 / 4 ( k ) = 5 1 / 4 ( 5 9 16 k 1 / 5 81 640 k 2 / 5 15 , 309 25 , 600 k 3 / 5 + 25 48 k 45 448 k 6 / 5 + 3 , 159 51 , 200 k 7 / 5 15 , 309 64 , 000 k 8 / 5 + 17 1 , 408 k 2 129 5 , 120 k 11 / 5 + 891 12 , 800 k 12 / 5 45 , 927 640 , 000 k 13 / 5 27 102 , 400 k 3 567 64 , 000 k 16 / 5 + 1 12 , 800 k 4 3 , 213 640 , 000 k 21 / 5 ) .

Proof

Utilizing Lemma 6 gives
W ( k , 5 / 4 ) 5 1 / 4 k 1 / 5 n = k [ 1 n 6 / 5 ( 1 + g l ( n ) ) ( 1 3 4 g l ( n ) + 21 32 g l 2 ( n ) ) ] = 5 1 / 4 k 1 / 5 n = k l 5 / 4 ( n ) ,
where
l 5 / 4 ( n ) = 1 n 6 / 5 9 40 n 7 / 5 243 3 , 200 n 8 / 5 15 , 309 32 , 000 n 9 / 5 + 1 40 n 11 / 5 + 27 1 , 600 n 12 / 5 + 5 , 103 32 , 000 n 13 / 5 3 3 , 200 n 16 / 5 567 32 , 000 n 17 / 5 + 21 32 , 000 n 21 / 5 .
Hence
W ( k , 5 / 4 ) 5 1 / 4 k 1 / 5 n = k ( 1 n 6 / 5 9 40 n 7 / 5 243 3 , 200 n 8 / 5 15 , 309 32 , 000 n 9 / 5 + 1 40 n 11 / 5 + 27 1 , 600 n 12 / 5 + 5 , 103 32 , 000 n 13 / 5 3 3 , 200 n 16 / 5 567 32 , 000 n 17 / 5 + 21 32 , 000 n 21 / 5 ) .
Using Lemma 2 and taking p = 6 / 5 , 7 / 5 , 8 / 5 , 9 / 5 , 11 / 5 , 12 / 5 , 13 / 5 , 16 / 5 , 17 / 5 , 21 / 5 in the left-hand side of inequality (13), respectively, we get
n = k 1 n 6 / 5 > 5 k 1 / 5 + 1 2 k 6 / 5 , n = k 9 40 n 7 / 5 > 9 16 k 2 / 5 9 80 k 7 / 5 21 800 k 12 / 5 , , n = k 567 32 , 000 n 17 / 5 > 189 25 , 600 k 12 / 5 567 64 , 000 k 17 / 5 3 , 213 640 , 000 k 22 / 5 , n = k 21 32 , 000 n 21 / 5 > 21 102 , 400 k 16 / 5 + 21 64 , 000 k 21 / 5 .
Adding up the above inequalities, we obtain
W ( k , 5 / 4 ) > L 5 / 4 ( k ) .

Theorem 2 is proved. □

Theorem 3 Let a n 0 ( n = 1 , 2 , ), 0 < n = 1 a n 5 / 4 < . Then
n = 1 ( 1 n k = 1 n a k ) 5 / 4 5 5 / 4 n = 1 ( 1 1 10 1 n 1 / 5 + η 5 / 4 ) a n 5 / 4 ,
(14)

where η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.46 is the best possible under the weight coefficient W ( k , 5 / 4 ) .

Proof

By Lemma 7, we have
n = 1 ( 1 n k = 1 n a k ) 5 / 4 k = 1 W ( k , 5 / 4 ) a k 5 / 4 .
Therefore, to prove inequality (14), it suffices to show that
W ( k , 5 / 4 ) 5 5 / 4 ( 1 1 10 1 k 1 / 5 + η 5 / 4 ) .
(15)

Obviously, inequality (15) becomes an equality for k = 1 . In what follows, we will assume that k 2 .

By Theorem 1 W ( k , 5 / 4 ) < R 5 / 4 ( k ) , we need only to prove that
R 5 / 4 ( k ) 5 5 / 4 ( 1 1 10 1 k 1 / 5 + η 5 / 4 ) .
Note that
η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.44 > 11 25 ,
it suffices to show
R 5 / 4 ( k ) 5 5 / 4 ( 1 1 10 1 k 1 / 5 + 11 / 25 ) .
(16)
Substituting k = x 5 in (16), inequality (16) becomes
R 5 / 4 ( x 5 ) 5 5 / 4 ( 1 1 10 1 x + 11 / 25 ) , where  x 2 5 ,
which is equivalent to the following inequality:
5 1 / 4 ( 5 133 240 x 17 , 689 144 , 000 x 2 + 25 48 x 5 19 192 x 6 17 , 689 480 , 000 x 7 + 467 4 , 224 x 10 + 133 18 , 000 x 11 + 97 38 , 400 x 15 + 133 60 , 000 x 16 + 61 504 , 000 x 20 + 19 240 , 000 x 25 ) 5 5 / 4 ( 1 1 10 1 x + 11 / 25 ) 5 133 240 x 17 , 689 144 , 000 x 2 + 25 48 x 5 19 192 x 6 17 , 689 480 , 000 x 7 + 467 4 , 224 x 10 + 133 18 , 000 x 11 + 97 38 , 400 x 15 + 133 60 , 000 x 16 + 61 504 , 000 x 20 + 19 240 , 000 x 25 5 1 2 1 x + 11 / 25 133 240 x 17 , 689 144 , 000 x 2 + 25 48 x 5 19 192 x 6 17 , 689 480 , 000 x 7 + 467 4 , 224 x 10 + 133 18 , 000 x 11 + 97 38 , 400 x 15 + 133 60 , 000 x 16 + 61 504 , 000 x 20 + 19 240 , 000 x 25 + 1 2 1 x + 11 / 25 0 f ( x ) 221 , 760 , 000 x 25 ( 25 x + 11 ) 0 ,
(17)
where
f ( x ) = 300 , 300 , 000 x 25 + 2 , 032 , 838 , 500 x 24 + 299 , 651 , 660 x 23 2 , 887 , 500 , 000 x 21 721 , 875 , 000 x 20 + 445 , 702 , 950 x 19 + 89 , 895 , 498 x 18 612 , 937 , 500 x 16 310 , 656 , 500 x 15 18 , 024 , 160 x 14 14 , 004 , 375 x 11 18 , 451 , 125 x 10 5 , 407 , 248 x 9 671 , 000 x 6 295 , 240 x 5 438 , 900 x 193 , 116 .
From the hypothesis x 2 5 > 1.14 , we have
300 , 300 , 000 x 25 + 2 , 032 , 838 , 500 x 24 + 299 , 651 , 660 x 23 2 , 887 , 500 , 000 x 21 721 , 875 , 000 x 20 + 445 , 702 , 950 x 19 + 89 , 895 , 498 x 18 > ( 300 , 300 , 000 × 1.14 4 + 2 , 032 , 838 , 500 × 1.14 3 + 299 , 651 , 660 × 1.14 2 2 , 887 , 500 , 000 ) x 21 721 , 875 , 000 x 20 + 445 , 702 , 950 x 19 + 89 , 895 , 498 x 18 = 1 , 020 , 861 , 716 x 21 721 , 875 , 000 x 20 + 445 , 702 , 950 x 19 + 89 , 895 , 498 x 18 = [ ( 1 , 020 , 861 , 716 x 721 , 875 , 000 ) x 2 + 445 , 702 , 950 x + 89 , 895 , 498 ] x 18 > [ ( 1 , 020 , 861 , 716 × 1.14 721 , 875 , 000 ) × 1.14 2 + 445 , 702 , 950 × 1.14 + 89 , 895 , 498 ] x 18 = 1 , 172 , 299 , 661 x 18 .
Further, we have
f ( x ) > 1 , 172 , 299 , 661 x 18 612 , 937 , 500 x 16 310 , 656 , 500 x 15 18 , 024 , 160 x 14 14 , 004 , 375 x 11 18 , 451 , 125 x 10 5 , 407 , 248 x 9 671 , 000 x 6 295 , 240 x 5 438 , 900 x 193 , 116 > 1 , 172 , 299 , 661 x 18 612 , 937 , 500 x 18 310 , 656 , 500 x 18 18 , 024 , 160 x 18 14 , 004 , 375 x 18 18 , 451 , 125 x 18 5 , 407 , 248 x 18 671 , 000 x 18 295 , 240 x 18 438 , 900 x 18 193 , 116 x 18 = 191 , 220 , 497 x 18 > 0 .

Consequently, inequality (17) holds true, and inequality (14) is proved.

Let us now show that η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.46 is the best possible under the weight coefficient W ( k , 5 / 4 ) .

Consider inequality (14) in a general form as
W ( k , 5 / 4 ) 5 5 / 4 ( 1 1 10 1 k 1 / 5 + η 5 / 4 ) .
(18)
Putting k = 1 in (18) yields
η 5 / 4 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] .

Thus the best possible value for η 5 / 4 in (18) should be η min = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] .

This completes the proof of Theorem 3. □

Remark 1 From the definition of W ( k , p ) and in the same way as in [17], we can establish the following accurate estimates of W ( 1 , 5 / 4 ) :
6.965042829 < W ( 1 , 5 / 4 ) < 6.967740323 .
(19)
Further, the approximation of η 5 / 4 can be derived as follows:
η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.46 .
Remark 2 For p = 5 / 4 , inequality (11) can be written as
n = 1 ( 1 n k = 1 n a k ) 5 / 4 5 5 / 4 n = 1 ( 1 1 ( 1 5 ) 5 / 4 W ( 1 , 5 / 4 ) n 1 / 5 ) a n 5 / 4 .
(20)
It is easy to observe that
1 10 1 n 1 / 5 + η 5 / 4 > 1 10 1 n 1 / 5 + 4 , 711 / 10 , 000 > 7 100 n 1 / 5
and
1 ( 1 5 ) 5 / 4 W ( 1 , 5 / 4 ) < 1 ( 1 5 ) 5 / 4 × 6.967740323 = 0.06808 < 7 100 ,
hence
1 ( 1 5 ) 5 / 4 W ( 1 , 5 / 4 ) n 1 / 5 < 1 10 1 n 1 / 5 + η 5 / 4 .

This implies that inequality (14) is stronger than inequality (11).

Declarations

Acknowledgements

The present investigation was supported, in part, by the Natural Science Foundation of Fujian province of China under Grant 2012J01014 and, in part, by the Foundation of Scientific Research Project of Fujian Province Education Department of China under Grant JK2012049.

Authors’ Affiliations

(1)
Department of Mathematics and Computer Science, Longyan University
(2)
Gangtou Middle School

References

  1. Hardy GH, Littlewood JE, Pólya G: Inequalities. 2nd edition. Cambridge University Press, Cambridge; 1952.Google Scholar
  2. Mitrinović DS, Pečarić JE, Fink AM: Inequalities Involving Functions and Thier Integrals and Derivatives. Kluwer Academic, Dordrecht; 1991.View ArticleGoogle Scholar
  3. Yang BC, Zhu YH: An improvement on Hardy’s inequality. Acta Sci. Natur. Univ. Sunyatseni 1998, 37(1):41–44.MathSciNetGoogle Scholar
  4. Huang QL:An improvement of series Hardy’s inequality for p = 3 . J. Hubei Inst. Natl. 1999, 17(3):54–57.Google Scholar
  5. Huang QL:A sharpness and improvement of Hardy’s inequality for p = 3 / 2 . J. Guangxi Norm. Univ. (Nat. Sci. Ed.) 2000, 18(1):38–41.Google Scholar
  6. Huang QL: An improvement of Hardy’s inequality in an interval. Acta Sci. Natur. Univ. Sunyatseni 2000, 39(3):20–24.MathSciNetGoogle Scholar
  7. Huang QL:An improvement of Hardy’s series inequality in the interval [ 2 , 5 ] . J. South China Univ. Technol. (Natl. Sci. Ed.) 2000, 28(2):64–68.Google Scholar
  8. Huang QL: An extension of a strengthened inequality. J. Guangdong Educ. Inst. 2001, 21(2):17–20.Google Scholar
  9. Yang BC: On a strengthened version of Hardys inequality. J. Guangdong Educ. Inst. 2005, 25(5):5–8.Google Scholar
  10. Kuang JC: Applied Inequalities. 4th edition. Shangdong Science and Technology Press, Jinan; 2010:576.Google Scholar
  11. Zhang XM: A new proof method of analytic inequality. RGMIA Research Report Collection 2009, 12(1):18–29.Google Scholar
  12. Zhang XM, Chu YM: New Discussion to Analytic Inequalities. Harbin Institute of Technology press, Harbin; 2009:260–275.Google Scholar
  13. Zhang, XM, Chu, YM: A new method to study analytic inequalities. J. Inequal. Appl. (2010). http://www.hindawi.com/journals/jia/2010/698012
  14. Yang L, Xia BC: Automated Discovering and Proving for Mathematical Inequalities. Science Press, Beijing; 2008:33–42. 117–142Google Scholar
  15. Yang L, Zhang JZ, Hou XR: Nonlinear Algebraic Equation Systems and Automated Theorem Proving. Shanghai Science’s and Technology’s Education Publishing House, Shanghai; 1996:137–166.Google Scholar
  16. He D:The automatic verification of Hardy inequality’s improvements and its improving type of P N . J. Guangdong Educ. Inst. 2012, 32(3):28–35.Google Scholar
  17. Deng, YP, He, D, Wu, SH: A sharpened version of Hardy’s inequality and the automated verification program. J. Math. Pract. Theory (2012, submitted)
  18. Huang YZ, He D:An improvement of Hardy’s inequality for p = 3 / 2 . J. Shantou Univ. (Natl. Sci. Ed.) 2012, 27(3):15–22.Google Scholar
  19. Yang BC: On a strengthened Hardy’s inequality. J. Xinyang Teach. Coll. (Natl. Sci. Ed.) 2002, 15(1):37–39.Google Scholar
  20. Huang QL:A strengthened Hardy’s inequality in the interval [ 1 , 2 ] . J. Guangdong Educ. Inst. 2002, 22(2):20–23.Google Scholar
  21. Huang QL, Yang BC: A strengthened dual form of Hardy’s inequality. J. Math. (PRC) 2005, 25(3):307–311.Google Scholar
  22. Zhu YH, Yang BC: Improvement on Euler’s summation formula and some inequalities on sums of powers. Acta Sci. Natur. Univ. Sunyatseni 1997, 36(4):21–26.MathSciNetGoogle Scholar
  23. Qian X, Meixiu Z, Zhang X: On a strengthened version of Hardy’s inequality. J. Inequal. Appl. 2012, 2012: 300. 10.1186/1029-242X-2012-300View ArticleGoogle Scholar

Copyright

© Deng et al.; licensee Springer 2013

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.